English to 14 - Lockwood, Liz (Oxford : Oxford University Press, 1996)
Covers the content and skills required by the National Curriculum. This book can be used to complement an existing course or independently by students. It includes a range of texts and features such as full coverage of speaking and listening, reading, and writing criteria, four end-of-chapter assignments. This book provides revision of grammar.
Keywords: English literature; English language Textbooks Secondary schools